Preparação e avaliação in vitro de nanofibras gelatina/policaprolactona com estrutura casca-núcleo obtidas por eletrofiação co-axial - Ildeu Helenio Lazarini Pereira (2013)
In this study, nanofibers containing polycaprolactone (PCL) and gelatin were produced by electrospinning. The combination of these two polymers in a core-shell structure was achieved by using a coaxial electrospinning technique. Nanofibers with this type of structure are good candidates for Tissue Engineering, since they are able to mimetize the structure of the extracellular matrix by combining the bioactivity of gelatin (natural polymer) with the biodegradability and high mechanical properties of polycaprolactone (synthetic polymer). Gelatin was submitted to a crosslinked reaction with glutaraldehyde in order to reduce its solubility in aqueous solutions Techniques such as FTIR, Transmission and Scanning Microscopies showed the morphology of the nanofiber obtained after changes in solution and electrospinning parameters were performed. In this work, it was also demonstrated the possibility of biomimetically coating the surface of the nanofibers with calcium phosphates after the immersion of the nanofibers in a SBF10 solution. The presence of gelatin as the shell material proved to be useful in favoring the deposition of the calcium phosphate surface layer. X ray diffraction results showed the presence of hydroxyapatite, one of the components of bone, in the composition of the obtained coating. In vitro studies confirmed the biocompatibility of the nanofibers. The mineralized nanofibers were able to favor both stem cell proliferation and differentiation of them in osteoblasts.